Selective Serotonin Reuptake Inhibitor Pharmacokinetics During Pregnancy: Clinical and Research Implications - Ethan A. Poweleit; Ethan A. Poweleit; Ethan A. Poweleit; Ethan A. Poweleit; Margaret A. Cinibulk; Sarah A. Novotny; Melissa Wagner-Schuman; Laura B. Ramsey; Laura B. Ramsey; Jeffrey R. Strawn; Jeffrey R. Strawn; Jeffrey R. Strawn (Frontiers Media S.A., 2022)
Pregnancy and associated physiologic changes affect the pharmacokinetics of many medications, including selective serotonin reuptake inhibitors-the first-line pharmacologic interventions for depressive and anxiety disorders. During pregnancy, SSRIs exhibit extensive pharmacokinetic variability that may influence their tolerability and efficacy. Specifically, compared to non-pregnant women, the activity of cytochrome P450 (CYP) enzymes that metabolize SSRIs drastically changes (e.g., decreased CYP2C19 activity and increased CYP2D6 activity). This perspective examines the impact of pharmacokinetic genes-related to CYP activity on SSRI pharmacokinetics during pregnancy. Through a simulation-based approach, plasma concentrations for SSRIs metabolized primarily by CYP2C19 (e.g., escitalopram) and CYP2D6 (e.g., fluoxetine) are examined and the implications for dosing and future research are discussed.